Interlaboratory Study of Quality Control Isolates for a Broth Microdilution Method (Modified CLSI M38-A) for Testing Susceptibilities of Dermatophytes to Antifungals - Ghannoum, M. A. (American Society for Microbiology, 2006)
The Clinical and Laboratory Standards Institute (CLSI; formerly National Committee for Clinical Laboratory Standards, or NCCLS) M38-A standard for the susceptibility testing of filamentous fungi does not specifically address the testing of dermatophytes. In 2003, a multicenter study investigated the reproducibility of the microdilution method developed at the Center for Medical Mycology, Cleveland, Ohio, for testing the susceptibility of dermatophytes. Data from that study supported the introduction of this method for testing dermatophytes in the future version of the CLSI M38-A standard. In order for the method to be accepted by CLSI, appropriate quality control isolates needed to be identified. To that end, an interlaboratory study, involving the original six laboratories plus two additional sites, was conducted to evaluate potential candidates for quality control isolates. These candidate strains included five Trichophyton rubrum strains known to have elevated MICs to terbinafine and five Trichophyton mentagrophytes strains. Antifungal agents tested included ciclopirox, fluconazole, griseofulvin, itraconazole, posaconazole, terbinafine, and voriconazole. Based on the data generated, two quality control isolates, one T. rubrum isolate and one T. mentagrophytes isolate, were identified and submitted to the American Type Culture Collection (ATCC) for inclusion as reference strains. Ranges encompassing 95.2 to 97.9% of all data points for all seven drugs were established.